PENGEMBANGAN PELAYANAN BAGI ANAK SEKOLAH MINGGU DENGAN ATTENTION-DEFICIT / HYPERACTIVITY DISORDER (ADHD) DI GEREJA TABGHA CABANG BATU AJI - Eko Agus Setiawan (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2023)
Jesus in His ministry once scolded His disciples who were disturbed by many people bringing small children to Him so that Jesus would touch them. Jesus welcomed the children with joy and blessed them. During the period of Christian education for Sunday School children, there are children who quickly accept the lessons given by their Sunday School teachers, but there are also children who have special needs, for example children with Attention-Deficit / Hyperactivity Disorder (ADHD). . This research was carried out with a literature study to find previous research results that support the problem being faced. It was found that in serving Sunday School children with ADHD, parents and Sunday School teachers need to collaborate and strive to create a friendly environment for them.